Convert the equation to logarithmic form: e =A) ln(m) = sB) ln(S) = mO In(e) = sD) In(e) = m
![Convert the equation to logarithmic form e A lnm sB lnS mO Ine sD Ine m class=](https://us-static.z-dn.net/files/d16/4461dd0151abe60d66ac7f11d9332a86.png)
The given equation is:
[tex]e^m=s[/tex]Take the natural log of both sides:
[tex]\ln e^m=\ln s[/tex]Apply the power rule of logarithms:
[tex]\begin{gathered} m\ln e=\ln s \\ Also\text{ }\ln e=1,\text{ then} \\ m*1=\ln s \\ m=\ln s \\ \text{ Reorder terms} \\ \ln(s)=m \end{gathered}[/tex]The answer is B. ln(s)=m